Motivations of collegiate drumming squad members - Noveno, Marielle M. 2002-
Collegiate drumming squads have been seen performing on different occasions, such as sporting and school events (Alosi, 2012). With the given schedule of collegiate events, training, classes, and studying outside class hours, managing these responsibilities could be mentally and physically taxing for its members. This study delved into the psychological aspects of collegiate drumming squad members, mainly focusing on exploring the motivations for continued participation and comparing and contrasting them across the different phases of the membership. The study is limited to the collegiate drumming squad members of the University of the Philippines. The drummer participants were active team members and were chosen using purposive sampling. Other study participants include close family members/friends of the drummer participants and their coaches. Semi-structured interviews were employed as the primary data collection method. The data collected were analyzed using deductive and inductive thematic analysis, which resulted in the identification of five main themes that cover participants' motivations: (a) interest and previous experiences, (b) personal growth and development, (c) strong team connection, (d) team devotion, and (e) role fulfillment. The results revealed that participants are polymotivated and that all themes connect to one strong motivation: overall enjoyment of being part of the team. Furthermore, findings showed that the longer members stayed in the team, the stronger their sense of leadership and the malasakit they exhibited.